(untitled) (Inovasi, 2023)
Food commodities are included in the volatile food category which is dominant in determining inflation because prices fluctuate so that they contribute to national and regional inflation. This study aims to analyze price stabilization and formulate policy recommendations to anticipate strategic food commodity price fluctuations in North Sumatra province. Using weekly secondary data, for the period January 2021-December 2022 (104 observations). Technical analysis using the ARIMA model and the Coefficient of Variation. The results of the analysis with reference to price stabilization indicators as a reference in stabilizing food supply and prices at the consumer level indicate that there are seven commodities that need immediate intervention, namely Dry Seed Soybeans, Cooking Oil, Chicken Eggs, Pure Beef, Wheat Flour and Sugar. Sand. Alternative policies in order to maintain the stability of food prices are (1) affordable prices, (2) availability of supplies, (3) smooth distribution and, (4) effective communication. These four strategies can be implemented in the form of (1) carrying out low-cost food market operations, (2) monitoring prices and daily supplies carried out by the Food Officers Unit, (3) conducting food commodity bazaars before and during the HBKN, (4) inter-governmental cooperation. Regional, (5) Efforts to provide food commodity supplies, (6) Active distribution of commodities to several markets in the North Sumatra region, (7) Intensive coordination with TPID with the Ministry of Trade and the Economic Bureau of the North Sumatra Provincial Government, (8) High Level implementation TPID meetings ahead of and during HBKN in several districts/cities of North Sumatra province, and (9) Use of Regional Incentive Funds to increase food availability. Keywords: ARIMA, price fluctuation, coefficient of variation, price stabilization